Whoops! - Simon, Mary Manz; Nang ChanYeema (New York, USA Concodia Publishing House, 1992)
An easy-to-read retelling of the trials of Jonah, who had trouble understanding the essence of God's love.
Keywords: Juvenile Nonfiction